Comparison of Postoperative Outcomes Between Primary MIS TLIF and MIS TLIF With Revision Decompression. Issue 2 (15th January 2019) - Khechen, Benjamin; Haws, Brittany E.; Patel, Dil V.; Narain, Ankur S.; Hijji, Fady Y.; Guntin, Jordan A.; Cardinal, Kaitlyn L.; Iyer, Sravisht; Singh, Kern
Abstract : Study Design: Retrospective cohort. Objective: To compare postoperative improvements in surgical and patient-reported outcomes (PROs) between patients undergoing minimally invasive laminectomy and minimally invasive transforaminal lumbar interbody fusion (MIS TLIF) as a primary procedure to patients undergoing MIS laminectomy and TLIF as a revision to primary lumbar decompression (LD). Summary of Background Data: MIS TLIF and LD have demonstrated to be effective surgical options for lumbar degenerative disease. However, some patients undergoing LD experience recurrent symptoms and eventually require a revision decompression with fusion. Methods: A prospectively maintained surgical database of patients who underwent a primary or revision one-level MIS TLIF for degenerative spinal pathology between 2014 and 2016 was reviewed. Consecutive patients undergoing primary MIS TLIF and revision lumbar discectomy and/or laminectomy were matched in a one-to-one fashion to primary MIS TLIF patients who had not undergone a previous LD by age and preoperative diagnosis. Differences in patient demographic, comorbidity, and perioperative characteristics between procedure groups were assessed using Pearson chi-squared analysis and Student t test for categorical and continuous variables, respectively. Improvements in PROs from preoperative values were compared between primary and revision cohorts using Student t tests. Pearson chi-squared analysis was used to compare rates of minimum clinically important difference achievement between procedure groups. Statistical significant was set at P  < 0.05. Results: A total of 52 patients were included in this analysis. Twenty-six underwent primary MIS laminectomy and TLIF and 26 underwent MIS TLIF with a revision decompression. No differences in baseline or perioperative variables were observed. Revision and primary MIS TLIF patients experienced similar improvements in PROs at all postoperative time points. Conclusion: The results of the present study demonstrate patients undergoing primary MIS TLIF with LD as a revision to a primary decompression experienced similar postoperative improvements in PROs as compared to primary MIS TLIF patients. This indicates a primary decompression does not compromise clinical outcomes in patients undergoing MIS TLIF. As such, patients should not be precluded from undergoing MIS TLIF based on the history of a previous LD. Level of Evidence: 3 Abstract : This study assesses postoperative improvements in surgical and patient-reported outcomes (PROs) between patients undergoing primary and revision minimally invasive transforaminal lumbar interbody fusion (MIS TLIF). No differences in operative variables or PRO improvements were observed. Therefore, primary and revision patients can expect similar outcomes after MIS TLIF.